Automated Known-Plaintext Cryptanalysis of Short Hagelin M-209 Messages. Issue 1 (2nd January 2016) - Lasry, George; Kopal, Nils; Wacker, Arno
Abstract: The Hagelin M-209 portable encryption device was used by the U.S. Army in World War II and the Korean War, as well as by other armies and in embassy settings. In this article, a fully automated, computerized known-plaintext attack is presented. It is based on hillclimbing and a novel fitness function: the aggregate displacement error. Performance evaluation shows that this attack is able to recover key settings for messages as short as 50 characters. To validate these results, several publicly available challenge messages were solved with this method, including a message with only 40 letters.